156k views
5 votes
If c = -2x2+ 3x and D = 4 - 3x then 2c - 3d is

1 Answer

7 votes

Final answer:

2c - 3D, with c = -2x^2 + 3x and D = 4 - 3x, results in the expression -4x^2 + 15x - 12.

Step-by-step explanation:

The student asked for the expression 2c - 3D when c = -2x^2 + 3x and D = 4 - 3x. First, we need to multiply c by 2 and D by 3 and then subtract the latter from the former.

Firstly, calculate 2c: 2(-2x^2 + 3x) = -4x^2 + 6x.

Then, calculate 3D: 3(4 - 3x) = 12 - 9x.

Next, subtract 3D from 2c: (-4x^2 + 6x) - (12 - 9x) = -4x^2 + 6x - 12 + 9x.

Combine like terms: -4x^2 + 15x - 12.

The resulting expression for 2c - 3D is -4x^2 + 15x - 12.

User Lindz
by
7.8k points